Topical Melatonin Improves Gastric Microcirculatory Oxygenation During Hemorrhagic Shock in Dogs but Does Not Alter Barrier Integrity of Caco-2 Monolayers - Truse, Richard; Nolten, Inga; Schulz, Jan; Herminghaus, Anna; Holtmanns, Tobias; Gördes, Lukas; Raupach, Annika; Bauer, Inge; Picker, Olaf; Vollmer, Christian (Frontiers in Medicine, 2020)
Systemic administration of melatonin exerts tissue protective effects in the context of hemorrhagic shock. Intravenous application of melatonin prior to hemorrhage improves gastric microcirculatory perfusion and maintains intestinal barrier function in dogs. The aim of the present study was to analyze the effects of a topical mucosal melatonin application on gastric microcirculation during hemorrhagic shock in vivo and on mucosal barrier function in vitro. In a randomized cross-over study, six anesthetized female foxhounds received 3.3 mg melatonin or the vehicle as a bolus to the gastric and oral mucosa during physiological and hemorrhagic (-20% blood volume) conditions. Microcirculation was analyzed with reflectance spectrometry and laser doppler flowmetry. Systemic hemodynamic variables were measured with transpulmonary thermodilution. For analysis of intestinal mucosal barrier function in vitro Caco-2 monolayers were used. The transepithelial electrical resistance (TEER) and the passage of Lucifer Yellow (LY) from the apical to the basolateral compartment of Transwell chambers were measured. Potential barrier protective effects of melatonin against oxidative stress were investigated in the presence of the oxidant H2O2. During physiologic conditions topical application of melatonin had no effect on gastric and oral microcirculation in vivo. During hemorrhagic shock, gastric microcirculatory oxygenation (µHbO2) was decreased from 81 ± 8% to 50 ± 15%. Topical treatment with melatonin led to a significant increase in µHbO2 to 60 ± 13%. Topical melatonin treatment had no effect on gastric microcirculatory perfusion, oral microcirculation or systemic hemodynamics. Incubation of H2O2 stressed Caco-2 monolayers with melatonin did neither influence transepithelial electrical resistance nor LY translocation. Topical treatment of the gastric mucosa with melatonin attenuates the shock induced decrease in microcirculatory oxygenation. As no effects on local microcirculatory and systemic perfusion were recorded, the improved µHbO2 is most likely caused by a modulation of local oxygen consumption. In vitro melatonin treatment did not improve intestinal barrier integrity in the context of oxidative stress. These results extend the current knowledge on melatonin’s protective effects during hemorrhage in vivo. Topical application of melatonin exerts differential effects on local microcirculation compared to systemic pretreatment and might be suitable as an adjunct for resuscitation of hemorrhagic shock.